Santau: the use of herbal medicine and restrictions in treatment - Mohd Yusoff, Ahmad Nasir; Ismail, Nik Rosniwati; Kassan, Mokhtar (Human Resources Management Academic Research Society (HRMARS), 2024)
Herbal medicine has long been a foundation of conventional medical practices and remains widely used today. In traditional Malay medicine, herbal remedies form a primary component often employed to treat various ailments. However, some Malaysians remain uncertain about the role and benefits of traditional medicine, such as herbs, as an alternative form of treatment, likely due to limited information on herbal remedies for disease management. Thus, this study aims to identify the types of herbal medicines used following the “Tepuk Daun Nangka” treatment, presenting them as a complementary medical approach that may significantly contribute to comprehensive healing for Santau (poisoning) patients. This case study involves the narrative of a male university lecturer who faced challenges in worship due to disturbances that affected his emotions and faith since 1998. The study data comprises experiences of a Santau patient who sought Islamic treatment using herbal medicine and observed specific restrictions after undergoing the Tepuk Daun Nangka treatment. The data gathered are essential for evaluating the effects of herbal remedies and post-treatment restrictions on Santau recovery efforts. Findings highlight the variety of herbal medicines used and their efficacy in treating Santau patients. Conclusively, this study supports the effectiveness of herbal medicine for Santau treatment. In the globalized era, it is crucial for society to accept herbal remedies as a natural approach to nurturing a healthy life and fostering well-rounded, healthy human capital, both physically and spiritually, to enable societal progress. These findings offer valuable insights into the effective use of herbal medicine as an alternative treatment that complements modern medical practices endorsed by the Ministry of Health Malaysia. Embracing this knowledge can pave the way for a more comprehensive and holistic approach to mental and physical healthcare, ultimately benefiting society at large.